2013
DOI: 10.1002/mus.23749
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome during childhood: Particular clinical and electrophysiological features

Abstract: Gait disorder, leg pain, a high rate of distal conduction block, and a good prognosis are among the main specific features of GBS in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
(112 reference statements)
1
15
1
6
Order By: Relevance
“…Moreover, Hiraga et al (3) stated that AMAN patients with a severe clinical picture could not regain their ability to walk in the first six months, and a complete healing could last a longer time. Devos et al (10) conducted a study on 19 children and reported that 17 of them were able to completely recover after more than a year. In our patient with a severe clinical picture, early healing was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hiraga et al (3) stated that AMAN patients with a severe clinical picture could not regain their ability to walk in the first six months, and a complete healing could last a longer time. Devos et al (10) conducted a study on 19 children and reported that 17 of them were able to completely recover after more than a year. In our patient with a severe clinical picture, early healing was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is triggered by a preceding respiratory or gastrointestinal infection in up to two thirds of cases. [5][6][7][8] Campylobacter jejuni is the most frequently found gastrointestinal pathogen in patients with GBS. Incidence rates vary between 0.38 and 2.53 per 100 000 based on region of the world.…”
mentioning
confidence: 99%
“…Overall, acute demyelinating inflammatory polyneuropathy is the most common variant occurring in 72% to 95% of cases. 7,8,10 There is male predominance in GBS, and the mean age is 4.9 (range, 5-7.5 years). [4][5][6][7]10,11 Presenting signs include weakness and areflexia or hyporeflexia in nearly all patients as well as neuropathy, with myalgias or leg pain and paraesthesias.…”
mentioning
confidence: 99%
See 2 more Smart Citations